Phosphoric acid recovery from concentrated aqueous feeds by a mixture of di-isopropyl ether (DiPE) and tri-n-butylphosphate (TBP): extraction data and modelling. Issue 12 (20th January 2017) - Assuncao, M. Campos; Cote, G.; Andre, M.; Halleux, H.; Chagnes, A.
Abstract : This paper reports experimental data and modelling about the extraction of H3 PO4 from concentrated aqueous feeds (3 to 14 M) by the mixture of DiPE and TBP at 25 °C: distribution ratios of H3 PO4 and water, and associated change of phase volume ratio. Abstract : This paper reports experimental data about the extraction of phosphoric acid from concentrated aqueous feeds (3 to 14 M H3 PO4 ) by the mixture of di-isopropyl ether (DiPE) and tri- n -butylphosphate (TBP) at 25 °C: distribution ratios of H3 PO4 and water, and change of phase volume ratio during extraction. Then, a simple model based on the extraction isotherms of H3 PO4 and water as well as on the mass balance of these two compounds is developed in the case of the mixture of 90% wt DIPE and 10% wt TBP that corresponds to the solvent used at the industrial scale for the production of purified phosphoric acid.